2019
DOI: 10.1177/0033354919849942
|View full text |Cite
|
Sign up to set email alerts
|

Writing Assignments in Epidemiology Courses: How Many and How Good?

Abstract: Objectives: Schools and programs of public health are concerned about poor student writing. We determined the proportion of epidemiology courses that required writing assignments and the presence of 6 characteristics of these assignments. Methods: We requested syllabi, writing assignments, and grading criteria from instructors of graduate and undergraduate epidemiology courses taught during 2016 or 2017. We assessed the extent to which these assignments incorporated 6 characteristics of effective writing assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The researcher found that they could not comprehend the text well in the experimental class and they were unable to understand all of the questions. (2,023). Therefore, the null hypothesis (H0) which suggested that there was no significant difference between the students' ability in reading comprehension who were treated through the collaborative learning method and the students who were taught using three phases technique was rejected.…”
Section: Results Of Students' Reading Comprehension 411 Scoring Classification Of Students Pre-testmentioning
confidence: 99%
“…The researcher found that they could not comprehend the text well in the experimental class and they were unable to understand all of the questions. (2,023). Therefore, the null hypothesis (H0) which suggested that there was no significant difference between the students' ability in reading comprehension who were treated through the collaborative learning method and the students who were taught using three phases technique was rejected.…”
Section: Results Of Students' Reading Comprehension 411 Scoring Classification Of Students Pre-testmentioning
confidence: 99%
“…We decided which factors should be included in our survey based on previous literature and recommendations for medical education. The factors incorporated into this study included lecture duration [ 13 – 15 ] and lecture frequency per week [ 13 , 16 , 17 ]; opportunities to take quizzes [ 18 , 19 ], submit assignments [ 20 , 21 ], give oral presentations [ 22 , 23 ], observe physicians’ practice [ 10 , 24 ], practice clinical skills [ 10 , 24 ], participate in interprofessional meetings [ 24 26 ], and interact with physicians [ 24 , 27 ]; and the frequency of technical Internet-related problems [ 28 ]. For details regarding the options for each answer, see S1 Method…”
Section: Methodsmentioning
confidence: 99%
“…Students create a document for their community partner through a series of assignments, including a proposed plan, peer review, and multiple revisions. The series of assignments require text and at least one visual element (such as a photograph, figure, table, or diagram); these assignments incorporate the seven recommended characteristics for writing assignments in Public Health (Anderson et al, 2020; August et al, 2019). The assignments are summarized in the supplementary material (see Supplemental Appendix) and can be obtained by emailing the authors.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a collection of six recommended characteristics for writing assignments was published to help instructors of higher education Public Health courses teach writing more effectively (August et al, 2019). These recommendations include (a) clearly describing the purpose of the writing and learning goals of the assignment, (b) requiring students to produce a document type (e.g., reports, policy briefs) used by public health workers, (c) asking students to write to a specific audience (e.g., low-literacy diabetes patients), (d) incorporating tasks that support writing development (e.g., peer review and revision), (e) requiring critical thinking about a real public health problem, and (f) providing clear assignment expectations (August et al, 2019). A seventh recommendation suggests that instructors require students to include a visual element such as a figure, table, or infographic in every assignment (Anderson et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation